2009
DOI: 10.1063/1.3126060
|View full text |Cite
|
Sign up to set email alerts
|

High coupling piezoelectric thin films of Pb(Zr,Ti)O3-based ternary perovskite compounds for GHz-range film bulk acoustic resonators

Abstract: We have deposited nearly stress-free single-crystal thin films of ͑001͒ Pb͑Mn, Nb͒O 3-Pb͑Zr, Ti͒O 3 ͑PMnN-PZT͒ on ͑001͒MgO substrates by rf-magnetron sputtering using a quenching process after the film growth. It is found that single c-domain/single-crystal thin films of PMnN-PZT containing 5%-10% PMnN show a strong hard ferroelectric response with 2E c Х 400 kV/ cm and P s Х 70 C / cm 2. GHz-range film bulk acoustic resonators incorporating PMnN-PZT thin films have been fabricated with microelectromechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The thickness electromechanical coupling factors k t for the films were evaluated by the relation k t 2 ¼ (p 2 /8)(k eff 2 )/(1 À k eff 2 ), where the effective coupling factors k eff were calculated from the resonant frequencies using FBAR structures. 24 It was found that the present PZTbased thin films show high coupling k t of more than 0.4. At the optimum composition, i.e., 6%PMnN-PZT(48/52), the film exhibited enhanced coupling k t ¼ 0.7, which could not be achieved in the conventional PZT ceramics.…”
Section: Dielectric and Ferroelectric Propertiesmentioning
confidence: 69%
See 1 more Smart Citation
“…The thickness electromechanical coupling factors k t for the films were evaluated by the relation k t 2 ¼ (p 2 /8)(k eff 2 )/(1 À k eff 2 ), where the effective coupling factors k eff were calculated from the resonant frequencies using FBAR structures. 24 It was found that the present PZTbased thin films show high coupling k t of more than 0.4. At the optimum composition, i.e., 6%PMnN-PZT(48/52), the film exhibited enhanced coupling k t ¼ 0.7, which could not be achieved in the conventional PZT ceramics.…”
Section: Dielectric and Ferroelectric Propertiesmentioning
confidence: 69%
“…35,36 As for wide-band GHz filters, 10%PMnN-PZT(55/ 45) thin films can be used to fabricate 3-GHz filter with 1-GHz bandwidth, based on the high coupling, k t $ 0.62. 24,37 IV. CONCLUSIONS Single-crystal thin films of PZT-based ferroelectric ceramics were fabricated, and their dielectric/piezoelectric properties were discussed.…”
Section: B Possible Applications Of Pzt-based Thin Filmsmentioning
confidence: 99%
“…Recently, thin films of ferroelectric piezoelectrics with thicknesses in the sub-μm range have received increasing attention for high frequency bulk acoustic resonators [15,16] as well as This work has been supported by imec's industrial affiliate program on beyond CMOS logic. S. T. King acknowledges financial support from the WiSys Technology Foundation and the Wisconsin Space Grant Consortium.…”
Section: Introductionmentioning
confidence: 99%
“…[4,20] Piezoelectric materials are widely applied in the fabrication of on-chip acoustic devices based on the technology of Miro-Electromechanical Systems (MEMS), [21][22][23] as filters, resonators, sensors, and the like. Although piezoelectricitybased phononic crystals with or without defects were pre-sented for the realization of acoustic forbidden bands [24][25][26][27] and guiding-wave modes, [28][29][30] the ASWs and ACT have not been created based on piezoelectric materials.…”
Section: Introductionmentioning
confidence: 99%